Simultaneous Bromate and Nitrate Reduction in Water Using Sulfur‐Utilizing Autotrophic and Mixotrophic Denitrification Processes in a Fixed Bed Column Reactor. Issue 9 (7th March 2014) - Demirel, Sevgi; Uyanık, İbrahim and Yurtsever, Adem and Çelikten, Hakan and Uçar, Deniz
<x xml:space="preserve">Abstract</x> Carcinogenic bromate (BrO3−) can be present in drinking water as a result of its formation from bromide (Br−) during ozonation. A fixed bed column reactor filled with elementel sulfur and limestone was operated for about six months under autotrophic and mixotrophic (autotrophic + heterotrophic) conditions at 30°C. The reactor was operated at the hydraulic retention time (HRT) ranging from 16.5 to 10.1 h at autotrophic conditions. Under mixotrophic conditions, 45 mg/L NO3‐N was removed completely at C/N ratio (mg CH3OH/mg NO3‐N) between 0.55 and 1.66 at HRT of 10.1 h. The average effluent pH was 7.8 and the sulfate concentration was lower than the Environmental Protection Agency limits at the mixotrophic stages. Efficient simultaneous BrO3− and nitrate removal was achieved at feed concentrations of 100–500 µg/L BrO3− and 45 mg/L nitrate under autotrophic and mixotrophic conditions. Effluent Br− measurements indicated that BrO3− was completely reduced without accumulation of by‐products.